2017
DOI: 10.1088/1752-7163/aa5cc5
|View full text |Cite
|
Sign up to set email alerts
|

Factors that influence the volatile organic compound content in human breath

Abstract: The large cohort of volunteers used here represents a unique opportunity to gauge the factors influencing VOCs profiles in a general population i.e. the most clinically relevant population. Classical clinical parameters and smoking habits clearly influence breath content and should therefore be accounted for in future clinical studies involving breath analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
95
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(106 citation statements)
references
References 63 publications
4
95
0
2
Order By: Relevance
“…To assess the influence of medication on exhaled VOC profiles we compared CKD 1 patients with and without antihypertensive drugs as CKD 1 patients form a fairly homogeneous group with respect to kidney function and medication. In agreement with Blanchet et al, medication did not have significant effects onto changes in breath profiles rather than the disease itself [60]. …”
Section: Discussionsupporting
confidence: 88%
“…To assess the influence of medication on exhaled VOC profiles we compared CKD 1 patients with and without antihypertensive drugs as CKD 1 patients form a fairly homogeneous group with respect to kidney function and medication. In agreement with Blanchet et al, medication did not have significant effects onto changes in breath profiles rather than the disease itself [60]. …”
Section: Discussionsupporting
confidence: 88%
“…In this study, we observed high interindividual variation for VOC profiles, which is in line with previous findings . We attempted to minimize interindividual variation by including only males within a specific age and BMI range, since it was recently shown that BMI, gender, and age influence the VOC profile . However, we still found substantial differences in the VOC profiles of the different participants of intervention 1.…”
Section: Discussionsupporting
confidence: 89%
“…One of those is the qualitative and quantitative interindividual and intraindividual variation in the VOCs in exhaled air . Concentrations of VOCs may vary considerably between individuals, for example, due to smoking, gender, age, and BMI . The intraindividual variation has received little attention so far.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The human body produces volatile organic compounds (VOCs) either physiologically or pathologically [7][8][9]. The identification of VOCs associated with specific pathological states and their use as potential biomarkers [10] is highly complex.…”
Section: Introductionmentioning
confidence: 99%